Tests and direct strength design on cold-formed steel channel beams with web holes. (1st April 2019) - Zhao, Jinyou; Sun, Kuo; Yu, Cheng; Wang, Jun
Highlights: Full-scale flexural tests on cold-formed steel channel beams with web holes. A non-linear finite element model was developed and verified against tests. The extensive finite element parametric analyses were carried out for study on direct strength method. The modified direct strength method formulas were proposed for cold-formed steel channel beams with web holes. Abstract: To investigate the flexural behaviors of cold-formed steel channel beams with web holes and assess the reliability of the current direct strength method (DSM) for design of cold-formed steel beams with web holes stipulated in North American Specification (NAS) (2016), ten groups of specimens with various sizes of web holes and lips were tested under four-point bending. Among them, each kind of specimens with short lips or long lips have five kinds of hole height-to-web depth ratios, 0, 0.2, 0.4, 0.6 and 0.8. It is shown that the web holes change the failure modes of beams from only distortional buckling or only local buckling to distortional-local buckling interaction controlled by distortional buckling or local-distortional buckling interaction controlled by local buckling. It is found that the moment capacities reduce slightly with a maximum reduction value of 7.0% when the ratio of hole height-to-web depth increases from 0 to 0.4, and that the moment capacities reduce dramatically with a maximum reduction value of 16.3% when the ratio of hole height-to-web depth further increases to 0.8. Moreover, ANSYS finite element (FE) program was used to simulate the beam tests, the simulation results show good agreement with the test results in terms of moment capacities and failure modes. Extensive ANSYS FE parametric analysis were carried out to verify the accurateness of critical elastic distortional buckling stress prediction method using CUFSM finite strip program and to modify the existed approximate prediction formulas of critical elastic local buckling stress applying to such beams with web holes. Furthermore, the test results and parametric analysis results were compared with the current DSM prediction results of cold-formed steel beams with web holes. It is found that the DSM in NAS (2016) provides unconservative predictions for most cold-formed steel channel beams with web holes, especially for beams failed by local-distortional buckling interaction controlled by local buckling. Therefore, the modified direct strength method formulas for cold-formed steel beams with web holes were proposed.